2022
DOI: 10.1002/naaq.10239
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Taurine Supplementation on Growth, Feed Utilization, Antioxidant Capacity, and Intestinal Microflora of Largemouth Bass Fed a Low Fish Meal Diet

Abstract: The present study was conducted to examine the effects of taurine supplementation on feed intake, growth, feed utilization, body composition, waste output, hepatic antioxidant enzymes, and intestinal microflora of Largemouth Bass Micropterus salmoides that were fed a low fish meal diet. Three isoproteic (49% crude protein) and isolipidic (9.5% crude lipid) diets were formulated: one diet contained 40% fish meal and served as the control (FM diet), and 60% of the fish meal in the FM diet was replaced by soybean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…In previous studies, the condition factors (CF) of 12.5 g largemouth bass (Micropterus salmoides) decreased with the further ratios of plant protein in the diets (Wu et al, 2021;Ren et al, 2022). These studies supported the CF results recorded in our trial.…”
Section: Discussionsupporting
confidence: 90%
“…In previous studies, the condition factors (CF) of 12.5 g largemouth bass (Micropterus salmoides) decreased with the further ratios of plant protein in the diets (Wu et al, 2021;Ren et al, 2022). These studies supported the CF results recorded in our trial.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, like SBM diets, 10% glycinin diets generally promoted the abundance of phylum Proteobacteria in the intestine of orange-spotted grouper vs. FM diets. The increased intestinal Proteobacteria abundance was also observed in largemouth bass fed SBM diets [ 62 ] and in hybrid grouper fed 10% glycinin diets [ 40 ]. Proteobacteria has many pathogenic bacteria that can secrete a large amount of lipopolysaccharides [ 63 ], and higher lipopolysaccharides levels exacerbate stroke by activating NF-κB and thus produce large amounts of pro-inflammatory cytokines [ 64 ].…”
Section: Discussionmentioning
confidence: 92%
“…Dietary factors may also influence the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR). An investigation by Ren et al (2022) demonstrated that the inclusion of taurine supplementation in largemouth bass diet resulted in a decrease in hepatosomatic index (HSI). The observed decrease in HSI among fish, which received taurine supplementation, could be attributed to liver function and reduced stress levels (Ren et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…An investigation by Ren et al (2022) demonstrated that the inclusion of taurine supplementation in largemouth bass diet resulted in a decrease in hepatosomatic index (HSI). The observed decrease in HSI among fish, which received taurine supplementation, could be attributed to liver function and reduced stress levels (Ren et al, 2022). In the present study, the comparison of G1 and G2 reveals an increase in HSI within the cypermethrin-exposed group.…”
Section: Discussionmentioning
confidence: 99%